Exam Ref MS-102 Microsoft 365 Administrator - Thomas, Orin 1973- (Pearson Education, Inc., 2024)
Prepare for the new Microsoft Exam MS-102 and help demonstrate your real-world mastery of the skills needed to help deploy and manage Microsoft 365 services in any environment. Focus on the expertise measured by these objectives: Deploy and manage a Microsoft 365 tenant Implement and manage identity and access in Azure AD Manage security and threats by using Microsoft 365 Defender Manage compliance by using Microsoft Purview This Microsoft Exam Ref: Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Provides exam preparation tips written by a top trainer, consultant, and sysadmin Assumes you have experience with the Microsoft 365 Admin Center and an understanding of Exchange Online, Skype for Business, SharePoint Online, Microsoft 365 ProPlus, Microsoft 365 Defender, Microsoft Purview and Microsoft Azure Active Directory The Exam Ref is the official study guide for Microsoft certification exams. Featuring concise, objective-by-objective reviews and strategic case scenarios and Thought experiments, exam candidates get professional-level preparation for the exam. The Exam Ref helps candidates maximize their performance on the exam and sharpen their job-role skills.
Includes bibliographical references and index
Keywords: Microsoft Office -- Study guides -- Examinations; Information technology -- Study guides -- Management -- Examinations; Microsoft software -- Study guides -- Examinations; Electronic data processing personnel -- Certification; Microsoft Office; Technologie de l'information; Gestion; Examens; Guides de l'étudiant; Logiciels Microsoft; Examens; Guides de l'étudiant; Electronic data processing personnel; Certification; Examinations; Microsoft software; Examinations; Study guides